Anaesthetic Management of a Parturient with Incidental Diagnosis of Ebstein Anamoly in COVID 19 Era-A Rare Case Report - Neha Yadav; Khushbu Rani; BK Sandhya; Simar Anand (Academia Anesthesiologica International, 2021)
Ebstein anamoly is a rare congenital disorder comprising less than 1% of patients with congenital heart diseases. Although it is rare, but this congenital cardiac anamoly is one of the most diverse in presentation, severity and management. Average life expectancy in the patients born with this anamoly is around 25-30 years. However, pregnancy in these patients is well tolerated but they are at increased risk of developing severe complications especially in the current scenario of covid 19. Here we present a case of 26-year-old, unbooked, primigravida patient with severe preeclampsia at period of gestation 32 weeeks for emergency cesarean section with unknown covid status. Patient was diagnosed with ebstein anamoly after presentation to hospital.